Pedro De Ángelis, the first 'delirious archivist' - Díaz de Zappia, Sandra L. (Revista General de Información y Documentación, 2020)
The expression “delirious archivist” was used by Umberto Eco to refer to Jorge Luis Borges when examining the influence that the work of the last one would have had in Eco´s written production. Nevertheless, the said expression was used previously, but in a different geographical and historical circumstances: the River Plate region in the middle of the XIXth century. Precisely, the aim of this article is firstly to identify the author and the recipient of the above mentioned affirmation, that is to say, Esteban Echeverría and Pedro De Ángelis; secondly, to establish which are the possible meanings of the term “archivist” that could have been applicable in Argentina by then.
Keywords: archivist's concept; Pedro De Ángelis; Esteban Echeverría; Archivo Americano y Espíritu de la Prensa del Mundo; River Plate